PERLINDUNGAN HAK TERSANGKA DALAM HAL PENAHANAN PADA TAHAP PENYIDIKAN DI POLRES PASAMAN BARAT - Muddasir, Muddasir (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
The human rights of the suspect in the case of detention as provided for in Articles 58, 59, 60, 61, 62 and 68 of the Criminal Procedure Code. At Pasaman Barat Police resort often violations when arrested. Issues discussed about the implementation of the protection of suspects' rights in detention at the investigation level at the Police of West Pasaman and the Investigator's Accountability at Pasaman Barat Police resort on violation of suspect's right in the case of detention. The research specification is analytical descriptive research with Normative juridical approach as the main approach and supported by juridical approach empirical. Based on the results of the first study, the protection provided by investigators at the Pasaman Barat Police Resort on suspects in the case of detention is the health care for the sick suspects, performing worship, contacting and receiving visits from relatives, sending and receiving letters to his legal counsel and his family. Another protection is the provision of suspension and transfer of forms of detention. Second; The responsibility of the investigator for violation The suspect's right to detention is the provision of compensation and rehabilitation. The accountability of the investigator by code of ethics is in the form of demotion / position and even dismissal when carrying out a strenuous act contrary to the code of ethics of the Police.